2010
DOI: 10.3109/01902141003790155
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of all-transretinoic acid–containing aerosol by inhalation to lungs in a guinea pig model system—A pilot study

Abstract: Systemic therapies with retinoic acid (RA) can result in toxic side effects without yielding biologically effective levels in target tissues such as lung. The authors adapted a PARI LC Star nebulizer to create a tubular system for short-term inhalation treatment of guinea pigs using a water-miscible formulation of all-trans RA (ATRA) or vehicle. Based on the initial average weight, animals received an estimated average ATRA doses of either 0.32 mg·kg −1 (low dose, 1.4 mM), or 0.62 mg·kg −1 (medium dose, 2.8 mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…In order to detect such a signal with a signal to noise ratio of at least 3 in extracts with our method under the described parameters, at least 3.7 g mouse liver would need to be extracted, which is approximately the weight of a whole mouse liver. However, this method is suitable for the determination of RA-isomers since we reported very recently the uptake of an all- trans RA aerosol to guinea pig lungs at detectable levels [17]. …”
Section: Discussionmentioning
confidence: 99%
“…In order to detect such a signal with a signal to noise ratio of at least 3 in extracts with our method under the described parameters, at least 3.7 g mouse liver would need to be extracted, which is approximately the weight of a whole mouse liver. However, this method is suitable for the determination of RA-isomers since we reported very recently the uptake of an all- trans RA aerosol to guinea pig lungs at detectable levels [17]. …”
Section: Discussionmentioning
confidence: 99%
“…The number of CFU was enumerated three weeks later. The dose for ATRA treatments was selected following a dose response study (data not shown), keeping in mind the level of toxicity previously reported for this compound (29,(51)(52)(53)(54)(55)(56)(57). Rifampicin was added to one treatment group to assess the adjunctive effect of ATRA.…”
Section: Mycobacterium Tuberculosis (H37rv) Infection and Growth In Vmentioning
confidence: 99%
“…In a 1987 safety assessment of retinyl palmitate and retinol, the Cosmetic Ingredient Review Expert Panel stated that these ingredients are safe as cosmetic ingredients in the present practices of use and concentration. 1 The Panel reviewed newly available studies since that assessment along with updated information regarding types and concentration of use 2 …”
Section: Resultsmentioning
confidence: 99%